(untitled) (Research, Society and Development, 2021)
It is possible to use digital media to both attract and retain patients, using this tool to disseminate knowledge, services and facilitate communication between potential customers and the clinic. Thus, it is essential that the dental surgeon is aware of the ethical concepts, present in the Dental Code of Ethics, when using advertising and marketing tools for their own benefit, in order to work with consistency and safety. The aim of this study is to characterize the benefits of digital marketing in dentistry, preconizing the Dental Code of Ethics. An integrative literature review was conducted using the descriptors "Ethic", "Dentistry" and "Digital Marketing", associated by the Boolean operators "and" and "or", through which 5 articles were selected, from the eligibility criteria proposed in the PRISMA ScR strategy, for qualitative analysis, in the Scielo, Pubmed and BVs databases. Digital marketing has been used as a strategy to promote dental services in contemporary times, and from this analysis, we conclude that digital marketing strongly contributes to the success of the dental surgeon, and can considerably affect his professional success. However, its use should be guided by conduct consistent with the Code of Dental Ethics, and knowledge of it by the dental surgeon is of great importance.